Cognitive impairment after intravenous thrombolysis in mild stroke: assessment of cerebral blood flow covariance network - Mei, Kefu; Li, Feng; Kang, Zhiming; Sun, Dong; Luo, Xuefei; Tian, Shiyuan; Zhang, Lei; Zhang, Junjian (Frontiers in Neurology, 2025)
BackgroundMild stroke may lead to cognitive impairment, and it remains unclear whether intravenous thrombolysis (IVT) can mitigate cognitive deficits. This study investigates whether IVT can help alleviate cognitive function impairment in patients and further explores changes in the topological properties of cerebral blood flow (CBF) networks.MethodsThis observational study prospectively enrolled 94 patients with acute mild ischemic stroke (44 IVT vs. 50 non-IVT) from two hospitals. A battery of neuropsychological tests and arterial spin labeling were performed to evaluate their cognitive functioning and CBF in 116 brain regions. Voxel-wise CBF was compared between patients and health controls. The CBF covariance network of patients was constructed by calculating across-subject CBF covariance among 116 brain regions. Network properties were calculated and compared between IVT and no-IVT groups.ResultsThe mild stroke group demonstrated significantly lower Montreal Cognitive Assessment (MoCA) scores compared to healthy controls (p < 0.001). Patients receiving IVT showed superior performance on the Trail Making Test-B (p = 0.043), Clock Drawing Test (p = 0.001), and Verbal Fluency Test (p = 0.033). Multivariate regression analysis adjusted for covariates demonstrated significant associations between IVT and cognitive outcomes: Montreal Cognitive Assessment (β = 2.85; 95% CI, 0.64–5.13), Trail Making Test-A (β = −16.90; 95% CI, −32.89–-0.90), Trail Making Test-B (β = −43.27; 95% CI, −78.78–-7.76), Hopkins Verbal Learning Test-Revised total recall (β = 3.57; 95% CI, 1.36–5.78), HVLT-R delayed recall (β = 1.53; 95% CI, 0.43–2.63), Clock Drawing Test (β = 7.09; 95% CI, 2.40–11.79), and Verbal Fluency Test (β = 3.00; 95% CI, 1.33–4.68). IVT patients exhibited higher small-worldness, clustering coefficient, and global efficiency of the network compared to non-IVT patients.ConclusionIntravenous thrombolysis demonstrated early cognitive benefits across multiple domains in patients with mild stroke. Improvement in the brain CBF covariance network properties may be the underlying mechanism.